JEV Infection Induces M-MDSC Differentiation Into CD3+ Macrophages in the Brain - Zhang, Nan; Gao, Xiaochen; Zhang, Weijia; Xiong, Junyao; Cao, Xiaojian; Fu, Zhen F.; Cui, Min (Frontiers in Immunology, 2022)
Japanese encephalitis virus (JEV) is one of the most important members of the flavivirus family. It is a typical zoonotic pathogen that has caused substantial social and economic losses worldwide. The conversion between JEV-induced immunosuppression and inflammatory responses has not been thoroughly investigated. In this study, cells infiltrating the brain tissue of JEV-infected mice were mainly identified as monocytic myeloid-derived suppressor cells (M-MDSCs), which subsequently differentiated into CD3+ macrophages. Co-cultured with T cells showed that both splenic M-MDSCs and brain infiltrated M-MDSCs isolated from JEV-infected mice inhibited T cell proliferation through ARG1 and iNOS. The splenectomy model revealed that JEV-induced M-MDSCs were mainly derived from bone marrow and migrated to the spleen and central nervous system (CNS). The results of the transcriptome analysis and IRF7-deficient mice indicated that the ZBP1-IRF7 signaling pathway played a central role in the induction of M-MDSCs and that JEV RNA induced the expression of ZBP1 and IRF7. M-MDSCs migrated into the CNS through the chemokine CCL2/N-CCL2 derived from astrocytes and differentiated into CD3+ macrophages through a mechanism mediated by M-CSF, IL-6 and IFN-γ in the brain microenvironment. These findings provide evidence on the pathway JEV regulates the differentiation of M-MDSCs and thereby exacerbate pathogenicity, which represents a potential therapeutic target for Japanese encephalitis.